Biometric Security and Privacy : Opportunities & Challenges in The Big Data Era - Al-maadeed, Somaya; Beghdadi, Azeddine; Bouridane, Ahmed; Crookes, Prof. Danny; Jiang, Richard (Switzerland. Springer, 2020)
This book highlights recent research advances on biometrics using new methods such as deep learning, nonlinear graph embedding, fuzzy approaches, and ensemble learning. Included are special biometric technologies related to privacy and security issues, such as quality issue, biometric template protection, and anti-spoofing. The book also focuses on several emerging topics such as big data issues, mobile biometrics and multispectral biometrics, and includes a number of new biometrics such as vein pattern, acoustic biometrics, eye-blinking EOG, ECG, gait and handwriting. Authors also show how to use biometrics in cyber security applications and its relevant legal matters under EU legislation. The contributors cover the topics, their methods, and their applications in depth.
Keywords: Big data; Biometrics (Biology).; Computer security; Image processing; Signal processing; Speech processing systems; System safety; User interfaces (Computer systems).; Signal, Image and Speech Processing; Big Data/Analytics.; Biometrics; Security Science and Technology; Systems and Data Security; User Interfaces and Human Computer Interaction